Patients’ preferences for systemic treatment of atopic dermatitis: safety and efficacy count the most - Schaarschmidt, Marthe-Lisa; Kromer, Daniel; Wellmann, Phoebe; Peitsch, Wiebke K.; Kromer, Christian (The journal of dermatological treatment, 2024)
Background: The advent of biologics and janus kinase inhibitors has revolutionized treatment of atopic dermatitis (AD). Objective: To investigate preferences of patients with AD for attributes of currently approved systemic treatments and assess influencing factors. Methods: An online discrete choice experiment was conducted in patients with AD throughout Germany to analyze preferences for outcome (probability of (almost) clear skin at week 16, probability of significant itch improvement, time to onset of itch relief and type of side effects) and process attributes (application method and frequency of laboratory tests). Results: Participants (n = 182, 75.3% female) considered side effects (Relative Importance Score (RIS): 31.2), (almost) clear skin (RIS: 24.2) and probability of itch improvement (RIS: 16.0) most important. Application method (RIS: 14.4), time to onset of itch relief (RIS: 7.4) and frequency of laboratory tests (RIS: 6.8) were less relevant. Preferences were significantly influenced by sex, age, psychiatric comorbidity, current therapy and health-related quality of life according to multivariate regression analysis. Conclusions: Participants attached great importance to safety and symptom control. However, preferences were also dependent on individual characteristics, underscoring the importance of personal counseling. Conjoined with medical considerations, patients’ preferences have fundamental impact on shared decisions for treatment of AD.